2011
DOI: 10.1021/jf200149a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Stages of Juice Processing on the Anthocyanin, Flavonol, and Procyanidin Contents of Cranberries

Abstract: Juice is the most common form in which cranberries are consumed; however there is limited information on the changes of polyphenolic content of the berries during juice processing. This study investigated the effects of three different pretreatments (grinding plus blanching; only grinding; only blanching) for cranberry juice processing on the concentrations of anthocyanins, flavonols, and procyanidins throughout processing. Flavonols and procyanidins were retained in the juice to a greater extent than anthocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
87
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 25 publications
13
87
0
1
Order By: Relevance
“…The flour produced by drying the pomace lost approximately 32% of the anthocyanin contents of its raw material, while the dried blueberries lost 42% of the anthocyanins present in fresh fruit. However, White et al (2011) found no significant differences (p > 0.05) in anthocyanin content after drying cranberry pomace at 40, 60 or 80 °C.…”
Section: Anthocyaninsmentioning
confidence: 65%
See 1 more Smart Citation
“…The flour produced by drying the pomace lost approximately 32% of the anthocyanin contents of its raw material, while the dried blueberries lost 42% of the anthocyanins present in fresh fruit. However, White et al (2011) found no significant differences (p > 0.05) in anthocyanin content after drying cranberry pomace at 40, 60 or 80 °C.…”
Section: Anthocyaninsmentioning
confidence: 65%
“…Cranberry residue was studied by White et al (2010White et al ( , 2011, who found means between 121.4 and 362.5 mg/100 g DW and only identified six peaks, lower than the anthocyanin content in the blueberry pomace, as quantified by the sum of the six anthocyanins whose concentrations were determined.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Several authors studied the stability of anthocyanins and procyanidins alongside the processing of berries into juice at laboratory scale [10,12,13]. However, little information has been published concerning the stability of bioactive compounds along the different processing steps of the production line of commercial berry juices.…”
Section: Commercial Juice Productionmentioning
confidence: 99%
“…For this reason, cranberries are usually processed into sweetened juices (Alasalvar and Shahidi 2013). However, there is extensive evidence to demonstrate that processing leads to significant loss of polyphenols, in particular anthocyanins (White et al 2011). Hot air drying is the most popular drying method due to low cost.…”
Section: Introductionmentioning
confidence: 99%